2013
DOI: 10.11118/actaun201361051405
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod diversity (Arthropoda) on abandoned apple trees

Abstract: In 2010 and 2011, the occurrence of arthropods on apple trees without management was monitored near the village of Velké Bílovice, South Moravia, in two selected localities (an abandoned apple tree orchard and a road apple tree alley). Arthropods in tree tops were killed using deltamehtrin applied with a fogger (Puls Fog). Each collection always contained the material from 5 trees in each site. In 2010, three collections were performed (28/4, 20/5, and 9/7), two in 2011 (11/5 and 23/6). Representatives of elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Heliophanus auratus, Agalenatea redii, Dictyna arundinacea) and epigeic species (Drassodes pubescens). Similar composition was found on cherry (Bucher et al, 2010) and apple trees (Šťastná and Psota, 2013) as well as on other fruit trees (Fišákova, 2013). The myrmecomorph salticid Synageles venator was the most common spider on the vine plants and its high occurrence was quite unusual.…”
Section: Sibianor Tantulus (Simon 1868)supporting
confidence: 67%
See 1 more Smart Citation
“…Heliophanus auratus, Agalenatea redii, Dictyna arundinacea) and epigeic species (Drassodes pubescens). Similar composition was found on cherry (Bucher et al, 2010) and apple trees (Šťastná and Psota, 2013) as well as on other fruit trees (Fišákova, 2013). The myrmecomorph salticid Synageles venator was the most common spider on the vine plants and its high occurrence was quite unusual.…”
Section: Sibianor Tantulus (Simon 1868)supporting
confidence: 67%
“…The myrmecomorph salticid Synageles venator was the most common spider on the vine plants and its high occurrence was quite unusual. In previous studies, this species was recorded as common from young cherry trees only (Bucher et al, 2010) but not from the old trees (Fišáková, 2013;Šťastná and Psota, 2013). It thus seems that the species is related to the bushes and small trees.…”
Section: Sibianor Tantulus (Simon 1868)mentioning
confidence: 75%
“…While metabarcoding found DNA traces from herbivorous Lepidopterans, which are pests of apple, and which by the time of sampling were in the larval stage, visual census showed few Lepidopteran species visiting the flowers. Apple orchards represent one of the most diverse cultivated agroecosystems with over 1000 arthropod species recorded (Szentkiralyi and Kozar, 1991;Šťastná and Psota, 2013). While pests are well known and described (Blommers, 1994), less is known about the communities of natural enemies and pollinators and how to augment them (Gomiero et To conclude, our study provides the starting point for a more complete overview of biodiversity of arthropod flower-visitors found in apple orchards.…”
Section: Comparison Between Metabarcoding and Visual Censusmentioning
confidence: 81%
“…Oak (Quercus robor L.) is particularly favoured as a host plant (Hawkins, 2003) but other tree species are also used including alder (Alnus glutinosa (L.)), hazel (Corylus avellana L.), beech (Fagus sylvatica L.), apple (Malus domestica Borkh. ), pear (Pyrus communis L.), cherry (Prunus avium L.), plum (Prunus domestica L.), and apricot (Prunus armeniaca L.) (Hill, 1987;Floren & Gogala, 2002;Gossner, 2008;Trautmann & Wetzler, 2011;Kehrli & Pasquier, 2012;Štastna & Psota, 2013;Belien et al, 2015;Bantock, 2018). Localised populations may become more adapted to feeding on particular host plant species, for example, a survey in Epping Forest, where beech trees are abundant, suggested that P. rufipes may have a greater preference for beech than oak, which is also abundant in this area (Dulwich, 1985).…”
Section: Distribution Food Sources and Host Rangementioning
confidence: 99%
“…In the UK, damage attributed to P. rufipes has been a particular problem in pears, where growers are not likely to apply early-season insecticides which risk suppressing populations of natural enemies (particularly anthocorids) that help to provide control of pear sucker, Cacopsylla pyricola (Foerster) (Solomon et al, 1989). Pentatoma rufipes can also be abundant in apple orchards (Hradil et al, 2013;Štastna & Psota, 2013), but the sprays applied for other pests (particularly blossom weevils and sawflies) may have helped to give secondary protection against P. rufipes. UK growers reported unprecedented levels of P. rufipes damage to apples in 2019, but the reasons for the sudden increased impact on this crop are unclear.…”
Section: Impact Of the Pestmentioning
confidence: 99%